2010
DOI: 10.1158/1078-0432.ccr-09-2591
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Activating and Inhibitory Fcγ Receptors by TLR7/8 Activation: Implications for Tumor Immunotherapy

Abstract: Purpose: Activation of Toll-like receptors (TLR) 7 and 8 by engineered agonists has been shown to aid in combating viruses and tumors. Here, we wished to test the effect of TLR7/8 activation on monocyte Fcγ receptor (FcγR) function, as they are critical mediators of antibody therapy.Experimental Design: The effect of the TLR7/8 agonist R-848 on cytokine production and antibodydependent cellular cytotoxicity by human peripheral blood monocytes was tested. Affymetrix microarrays were done to examine genomewide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…This suggests the opportunity of using VTX-2337 in combination with approved mAbs, where ADCC contributes to the clinical efficacy (17). The potential for TLR agonists to enhance NK cell function and increase ADCC have been documented in previous publications (21,(38)(39)(40). For example, CpG ODN has been reported to increase IFNg production of NK cells and enhance trastuzumab-mediated lysis of breast cancer cells and rituximab-mediated lysis of lymphoma cells (21,39).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This suggests the opportunity of using VTX-2337 in combination with approved mAbs, where ADCC contributes to the clinical efficacy (17). The potential for TLR agonists to enhance NK cell function and increase ADCC have been documented in previous publications (21,(38)(39)(40). For example, CpG ODN has been reported to increase IFNg production of NK cells and enhance trastuzumab-mediated lysis of breast cancer cells and rituximab-mediated lysis of lymphoma cells (21,39).…”
Section: Discussionmentioning
confidence: 87%
“…For example, CpG ODN has been reported to increase IFNg production of NK cells and enhance trastuzumab-mediated lysis of breast cancer cells and rituximab-mediated lysis of lymphoma cells (21,39). The TLR7/8 agonist resiquimod has also been shown to enhance FcgR function and ADCC and enhance the antitumor effect of HER2-targeted mAb therapy in a mouse model (40). Interestingly, we did not observe IFNg induction (Table 1) or the enhancement of ADCC by CpG ODN2006 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pam2CSK4 Enhances Antibody Therapy in Vivo-We next tested whether Pam2CSK4 could enhance antibody-mediated antitumor responses using a murine model of antibody therapy (22)(23)(24). Here, syngeneic CT26 colon adenocarcinoma cells engineered to express human Her2/neu were injected into the flanks of Balb/cJ mice.…”
Section: Tlr2 Modulates Mir-155 and Ship-resultsmentioning
confidence: 99%
“…Cells were centrifuged and resuspended at 10 ϫ 10 6 cells/ml in RPMI 1640. The murine tumor model (22) was used as described previously (23,24). Briefly, 5-week-old female Balb/cJ mice (The Jackson Laboratory, Bar Harbor, ME) were injected subcutaneously with 1 ϫ 10 6 of syngeneic CT26-HER2/neu cells.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Butchar and colleagues showed that TLR7 ligands improve the outcome of treatment with monoclonal antibodies by increasing Fc-g receptor expression and thus enhancing antibody-mediated cellular cytotoxicity (43). We have shown earlier that application of TLR7-activating RNA oligonucleotides can prevent growth of NK cell-sensitive tumors by activation of NK cells via TLR7-expressing DCs (44).…”
Section: Discussionmentioning
confidence: 98%